PEMANFAATAN LIMBAH KERANG DARAH SEBAGAI MATERIAL BUATAN AGREGAT KASAR BERDASARKAN NILAI KUAT TEKAN - Fistcar, Wawarisa Alnu; Utami, Sri Rejeki Laku; Fitriyanti, Aghni (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2021)
Abstract Construction of buildings using concrete is more popular than the use other materials. As an alternative to utilizing waste around the environment, it is necessary to innovate concrete mixtures with other materials.In this study, waste anadara granosa shell were used basic material for coarse aggregate in a concrete mixture, with variation andora granosa material 20%, 50% and 80%. Manufacture of cylindrical specimens measuring 15 x 30 cm to be tested for compressive strength at the age of 7, 14 and 28 days. This experiment uses normal concrete quality Fc = 25 MPa as a comparison control. The sample used in this study was 3 pieces in each variation, as well as using the compressive strength frequency analysis. The results of the concrete research without the addition waste anadara granosa shell a compressive strength is 34.54 MPa. Concrete with the addition of a mixture 20% anadara granosa shell a compressive strength 26,04 MPa, concrete with addition of a mixture 50% anadara granosa shelll a compressive strength 17,55 MPa, and concrete with addition of mixture 80% anadara granosa shell a compressive strength 9,62 MPa. So that the greater the percentage of adding blood clamshells will reduce the compressive strength, but the addition of 20% shells still meets the design quality concrete. Keywords : Anadara granosa shell, Concrete, Compressive streng